Corpus-Based Language Learning Among EFL Learners in an Environmental Context - Handoko, Handoko; Kaur, Sheena; Lau, Su Kia (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: This research presents a case study on the valuable contribution of corpus linguistics to English instruction with an environmental focus, aiming to raise environmental awareness among students. The study explores the role of corpus linguistics as an effective tool for teaching English in the context of comprehending and discussing environmental issues. Methodology: To achieve this, the research utilizes the News on the Web (NOW) corpus to identify common vocabulary in environmental texts. The study was conducted with a group of 13 students in a Specialized Listening and Speaking class, with an intermediate level of English proficiency. The research was conducted over three terms. Initially, students were provided with 75 words from the News on the Web (NOW) corpus, complete with definitions and example sentences. Subsequently, they were tasked with writing three sentences for each word and memorizing their usage within an environmental context. Finally, the students were tested by having to provide talks on 15 randomly selected words. Findings: The research findings indicate that 10 students were able to proficiently use 60.51% of the environmental words, while three students encountered difficulties in using these terms within the environmental context. Seven students demonstrated their ability to connect sentences coherently, utilizing proper grammar and pronunciation. Conclusion: This research suggests that most students successfully integrated environmental lexical items into their speaking, showcasing proficiency in grammar and pronunciation. However, most of the students (11 out of 13) require further support in structuring their speech cohesively. Rather than constructing a coherent narrative, they often employ words in isolation. Originality: This underscores the importance of using corpus-based methods to provide relevant vocabulary and fostering the skills necessary for constructing well-structured and cohesive speeches.